2023
DOI: 10.1002/ansa.202200066
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of Raman spectroscopy for the analysis of bacteria

Abstract: Rapid and sensitive bacteria detection and identification are becoming increasingly important for a wide range of areas including the control of food safety, the prevention of infectious diseases, and environmental monitoring. Raman spectroscopy is an emerging technology which provides comprehensive information for the analysis of bacteria in a short time and with high sensitivity. Raman spectroscopy offers many advantages including relatively simple operation, non‐destructive analysis, and information on mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…Nanoparticle arrays hold promising applications across diverse fields. They can serve as sophisticated photonic structures, finding utility in structural coloration and advanced optical biosensing [ 70 , 74 , 75 ]. Furthermore, they offer the potential to develop electronic nano-devices and chemical/biological sensors.…”
Section: Static Assembly Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticle arrays hold promising applications across diverse fields. They can serve as sophisticated photonic structures, finding utility in structural coloration and advanced optical biosensing [ 70 , 74 , 75 ]. Furthermore, they offer the potential to develop electronic nano-devices and chemical/biological sensors.…”
Section: Static Assembly Methodsmentioning
confidence: 99%
“…Table 1 provides the advantages and disadvantages of each assembly technique studied in this review. Static methods like layer-by-layer assembly [ 51 , 52 , 53 , 58 , 59 , 60 , 61 , 62 ] and template-assisted assembly [ 2 , 10 , 16 , 29 , 70 , 72 , 73 , 74 , 75 ] may need specific substrates. Polymer brushes [ 83 , 84 , 85 , 86 ] offer adjustability but risk aggregation.…”
Section: Comparative Analysis Of Static and Dynamic Methods: Challeng...mentioning
confidence: 99%
“…Since Raman spectroscopy always samples all biomolecules inside the probing volume, most Raman methods are phenotypic which means the information of all biomolecules can be found in the Raman spectra of bacteria [ 15 , 16 , 17 , 18 , 19 ]. In principle, there are two types of Raman measurements of bacteria—bulk samples and single-cell measurements.…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…In a recent review, Rodriguez et al [ 40 ] conclude that the use of advanced data processing methods will allow for a better interpretation of Raman spectra and the detection of minor differences in biological samples. Since it might be a problem to compare the results obtained from different data processing programs, future work should address this problem by developing a universal tool or database for more reliable results [ 40 ]. In our recent studies we showed that differentiation of bacteria and yeasts after standardized growth conditions using microbial bulk material for spectral recording was possible [ 11 ].…”
Section: Introductionmentioning
confidence: 99%